(untitled) (Journal of the College of Basic Education, 2023)
The subject of artistic handicrafts is considered one of the important topics in art education as it develops the student’s skills of concentration, imagination, analysis, application and creative thinking. Therefore, the researcher sees the need for this research, as it will deal with the art of applique (textile material) and apply the strategy of the skill course to help employ the material in an innovative way. Presenting a new vision for the use of appliqué art in designing a work of art, and trying to give the material a new look that surpasses both the technical and functional aspects.Therefore, the current research aims to identify (the effect of the skill cycle strategy in developing the art of applique among middle school students in art education).The researcher adopted the experimental method by selecting two samples from the middle school students (fifth grade), Belqis Preparatory School for Girls, affiliated to the General Directorate of Education, Rusafa First. Their number was (60) students, divided into (30) students for the experimental group and (30) students.The skill cycle strategy was applied because this strategy focuses on four important phases (perceives, retrieves, plans, performs). In order to achieve the goal of the research, the researcher prepared a set of teaching plans designed according to this strategy, a skill performance test form, and a cognitive achievement test for the sample students.In order to statistically process the data, the researcher used the following equations (the statistical bag (spss), through which each of the t-tests for two independent samples was extracted - the coefficient of difficulty and ease of the objective paragraph - the equation of the effectiveness of wrong alternatives - the correlation coefficient of Point Pacerial - Couder - Richardson equation 20) The results showed the following: 1- There is a statistically significant difference between the experimental and control groups in post cognitive achievement, in favor of the experimental group. 2- The results showed that there is a statistically significant difference between the experimental and control groups in the skill (designing the kosha) in favor of the experimental group. 3- There is a statistically significant difference between the experimental and control groups in the design of (pencil holder) in favor of the experimental group. 4- There is a statistically significant difference between the experimental and control groups in the skill (handbag design) in favor of the experimental group. 5- There is a statistically significant difference between the experimental and control groups in the skill (form of an educational book) in favor of the experimental group. 6- There is a statistically significant difference between the experimental group and the control group in the skill of designing (kitchen bra) in favor of the experimental group. 7- The results showed that there is a statistically significant difference between the experimental and control groups in the skill of designing (table cloth) in favor of the experimental group. 8- The results showed that there is a statistically significant difference between the experimental and control groups in all tests in favor of the experimental group. 9- There is an effect in the use of the skill cycle strategy in cognitive achievement for the benefit of the experimental group students. 10- The skill cycle strategy has an impact on the skill performance variable in favor of the experimental group students.